PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS VIII SMP NEGERI 2 TOMPASO - Farly J Ignatius Tandaju; Meyke Paat; Fransiska Harahap (LPPM Politeknik Saint Paul Sorong, 2023)
This study attempts to ascertain how student learning outcomes in science classes for Class VIII SMP NEGERI 2 Tompaso are affected by learning discipline. The population used in this study were all 50 class VIII students and 44 students were taken as a sample. Regression and correlation research, which is a statistical technique used to measure the strength of influence and the relationship between 2 variables and also to be able to determine the form of the relationship between 2 variables with quantitative results, were used by the researchers in this study as a quantitative approach. Based on the findings of the study, it can be inferred that learning discipline affects students' learning outcomes in the following ways: Based on the analysis results obtained Ȳ = 60.627 + 0.217. This implies that as variable X (learning discipline) increases, it has an influence on variable Y (student learning outcomes) 21.8%. Based on the results of the analysis of the correlation coefficient, a value of 0.467 was obtained, which means that there is an influence between variable X (learning discipline) and variable Y (learning outcomes) at a 5% and the relationship is moving in a constructive manner. The results of the determination test with a value of r² = 21.8%, this shows that the magnitude of the contribution of the influence of learning discipline on student learning outcomes is 21.8% while 78.2% is influenced by other unknown factors. After testing the hypothesis, the results obtained are tcount > ttable, namely 3.219> 1.682 at a value of a= 0.05 with degrees of freedom df=n-2 df=44-2=42. This indicates that either Ho is rejected and H1 is approved or that the Learning Discipline variable significantly affects Student Learning Outcomes.